The correlation between pre-operative serum tumor markers and lymph node metastasis in gastric cancer patients undergoing curative treatment. (November 2013) - Li, Fangxuan; Li, Shixia; Wei, Lijuan; Liang, Xiaofeng; Zhang, Huan; Liu, Juntian
Abstract Background: There was few study concentrated on the correlation between the evaluated tumor markers and lymph node metastasis. In this study, we aimed to evaluate the correlation between the CA724, CA242, CA199, CEA and the lymph node metastasis of gastric cancer and assess the prognostic value of them in different N stage patients. Methods: We analyzed the correlation between serum level of CA724, CA242, CA199, CEA and lymph node metastasis in 1501 gastric cancer patients. Results: Lymph node metastasis of gastric cancer was related with tumor location, Bormann type, tumor size, histological type, depth of invasion and TNM stage (p < 0.05). The values of CA724, CA242, CA199 and CEA were positively correlated with the metastatic lymph node counts and the N stage (p < 0.05). The later the N stage was, the levels of CA724, CA242 and CA199 were higher. The later the N stage was, the positive rates of tumor markers were higher (p < 0.05). In comparing with single tumor markers, the positive rates of tumor markers combination were higher. The combination of CA724 + CA242 + CA199 + CEA had highest positive rate. The higher CEA level related to N1 stage patients while higher CA199 was related with poor prognosis for N1 stage patients. For N0 and N2 stage patients, evaluation of CA724 indicated poorer prognosis. For N1 and N2 stage gastric patients, the patients with increased CA242 inclined to have shorter survival time. Conclusions: The tumor makers CA724, CA242, CA199 and CEA were evaluated significantly in the gastric patients with later N stage. The combination of these four tumor markers maybe prefer diagnostic index of gastric cancer and its lymph node metastasis. These tumor markers can be a possible indicator of poorer prognosis in different N stage patients.